Dynamic model of rotor blade behaviour - Szilágyi Dénes (Review of faculty of engineering : analecta technica Szegedinensia, 2009)
There are more than 40 Ka-26 rotorcrafts today in Hungary. They have glass-fibre composit e rotor blades had been constructed (at 1969) there were possibilities only for the static strengths analysis. Conversely the rotor blades are loaded by a lot of basically unsteady effects. For determination of them nowadays much more concinnity methods (theoretic examinations for exampl e vortex theories; 1:1 rale wind tunnel tests: flight tests) are used. Unfortunately such methods are very expensive and they often give different results. For the successful calculation of dynami c loads of a rotor blade (mainly by a bottom blade of a coaxial system) with the possibilities are available for me in Hungary. I had to develop such method thai has a satisfactory accuracy, take into consideration the unsteady effects, and easy realisable and usable with a PC. In this paper I presented analysis of aerodynamic-dynami c behaviour of the bottom rotor blade and the relation between the static and dynamic loads of the bottom rotor blade of coaxial rotor system using that aerodynamic-dynamic-aero elastic model. Results could give the base of the life time limit lengthen of that blades as validated by the present exploration.